Leflunomide-Induced Cystoid Macular Edema: A Rare Case Report - João, Alves Ambrósio; Catarina, Pestana Aguiar; Pedro, Cardoso Teixeira; João, Cardoso Costa; João, Chibante Pedro; Miguel, Ruão (Journal of Ophthalmic Science, 2024)
Introduction Cystoid macular edema (CME) is a sight-threatening condition caused by fluid accumulation in the macula due to blood-retinal barrier disruption. Various factors, including drug reactions, can lead to retinal fluid leakage. Leflunomide, a disease-modifying anti-rheumatic drug, marked significant progress in managing rheumatoid arthritis. Although effective, Leflunomide has rarely been linked to CME. This report presents a unique case of Leflunomide-induced CME, adding to the limited literature on this subject. Methods We report the case of a 75-year-old female with rheumatoid arthritis treated with Leflunomide, presenting with bilateral CME and reduced visual acuity (VA). Comprehensive ophthalmic evaluations, including VA tests, fundus examination, and optical coherence tomography, were conducted. Results The patient presented with CME and decreased VA in both eyes for several months. She had undergone cataract surgery 20 years prior and was using topical nepafenac, dorzolamide, and dexamethasone. Initial VA was OD 20/50 and OS 20/40. VA improved with treatment, but CME recurred upon discontinuation. The patient had been on Leflunomide for one year. After consulting with the Rheumatology department and considering a previous case of bilateral Leflunomide-induced CME, the drug was discontinued. CME resolved without recurrence or the need for topical treatment. At her final visit, VA was OU 20/25. Conclusion This case highlights Leflunomide as a potential, though rare, cause of CME. It emphasizes considering systemic medications in CME diagnosis. Timely discontinuation of Leflunomide may resolve CME and prevent further visual impairment. Further studies are needed to understand this rare side effect comprehensively.
Keywords: Leflunomide; Macular Edema; Drug-Related Side Effects and Adverse Reactions; Arthritis; Rheumatoid